2020
DOI: 10.1126/science.aba0803
|View full text |Cite
|
Sign up to set email alerts
|

A genetic mechanism for sexual dichromatism in birds

Abstract: Sexual dichromatism, a difference in coloration between males and females, may be due to sexual selection for ornamentation and mate choice. Here, we show that carotenoid-based dichromatism in mosaic canaries, a hybrid phenotype that arises in offspring of the sexually dichromatic red siskin and monochromatic canaries, is controlled by the gene that encodes the carotenoid-cleaving enzyme β-carotene oxygenase 2 (BCO2). Dichromatism in mosaic canaries is explained by differential carotenoid degradation in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 61 publications
(19 reference statements)
1
58
0
Order By: Relevance
“…Birds with low levels of background divergence have served as particularly powerful non-model systems for discovering the genetic bases of melanin and carotenoid coloration6, 8,11,12,14,18,20,[26][27][28], as they often exhibit discrete feather patches that differ in color and pigment type across the body19. Yet, despite the substantial variation in pigmentation across birds, the genetic bases of melanin and carotenoid coloration have only rarely been studied together in the same system (but see 11,14,16), though the genes involved are not currently known to overlap in function or co-localize in the genome3,5.…”
Section: Introductionmentioning
confidence: 99%
“…Birds with low levels of background divergence have served as particularly powerful non-model systems for discovering the genetic bases of melanin and carotenoid coloration6, 8,11,12,14,18,20,[26][27][28], as they often exhibit discrete feather patches that differ in color and pigment type across the body19. Yet, despite the substantial variation in pigmentation across birds, the genetic bases of melanin and carotenoid coloration have only rarely been studied together in the same system (but see 11,14,16), though the genes involved are not currently known to overlap in function or co-localize in the genome3,5.…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones such as androgen may indirectly influence the expression of androgen-regulated genes, through binding to transcription factors that interact with regulatory elements such as enhancer and cause sex-biased gene expression, which leads to sex-specific phenotypes ( Coyne et al 2008 ; Mank 2009 ). Whereas male plumage appears to be testosterone-dependent in passerines ( Kimball 2006 ), the molecular mechanisms controlling sex-biased gene expression and development of sexually dimorphic traits in birds is largely unknown ( Kraaijeveld 2019 ; Gazda et al 2020a ). In this study, we identified potential TFs that may regulate the expression of the red plumage color gene CYP2J19 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, even in the face of apparent strong constraint, sexual dimorphism can evolve rapidly (Stewart and Rice 2018) and differ strongly between closely related species (Owens and Hartley 1998). In at least some cases, dichromatism may evolve by a simple molecular mechanism at a single locus (Gazda et al 2020). Although it is clear that the majority of the color evolution in European butterflies is shared between the sexes, it remains an open question whether this reflects substantial unresolved antagonistic selection.…”
Section: Discussionmentioning
confidence: 99%